(untitled) (AYUSHDHARA, 2025)
Panchabhautika taila (PBT) a formulation explained in Kashyapa Samitha Kalpasthana is said to strengthen the psycho somatic condition of children exclusively, when used as Nasya. This formulation is indicated in the disorders of eye, head, oral cavity, neurological disorders like dumbness deafness etc. PBT not only supports the healthy milestones or growth of children but also prevents many early onsets of diseases like premature greying of hairs, vision problems, disorder of sleep and concentration etc. The present-day school going children are facing so many health hazards like vision issues, audibility, sleep disorders along with concentration lacuna as they are constantly exposed to radiation of mobile, TV, smart board etc. which are the hazards of modern lifestyle changes. Thus, this formulation which is said to strengthen the psycho somatic condition of children was selected and evaluated for its nutritional aspects. The analytical study revealed that this formulation contains calcium, potassium, iodine, iron, vitamin B1, vitamin E in specified concentration. This confirms that Panchabhautika taila is a nutritional combo pack for children if instilled as Nasya (nasal drops) which supports the concept of formulation Smriti Medha Vapur Balam (strengthens the memory, intellect and body) as explained in Kasyapa Samhita.